2022
DOI: 10.21203/rs.3.rs-1973470/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterologous third and fourth dose vaccine to reduce severity and mortality in COVID-19 patients during delta and omicron predominance: A cohort study in Chiang Mai, Thailand

Abstract: Background The Coronavirus disease 2019 (COVID-19) pandemic has evolved quickly, with numerous waves of different variants of concern resulting in the need for countries to offer continued protection through booster vaccinations. To ensure adequate coverage, Thailand has proactively adopted heterologous vaccination schedules. While studies have assessed homologous schedules in detail, the effectiveness of heterologous booster vaccine schedules against severity and mortality of COVID-19 patients, particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Covid-19 vaccination policies recommending the bivalent mRNA-booster vaccines as a fourth dose are mainly supported by studies on immunogenicity where some have shown higher induction of antibody levels against omicron subvariants including BA.4-5 compared with monovalent boosters. [4][5][6][7][8] Previous observational effectiveness studies of fourth dose monovalent vaccination, primarily on data from before BA.4-5 subvariant predominance, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] also lend some indirect support to these recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Covid-19 vaccination policies recommending the bivalent mRNA-booster vaccines as a fourth dose are mainly supported by studies on immunogenicity where some have shown higher induction of antibody levels against omicron subvariants including BA.4-5 compared with monovalent boosters. [4][5][6][7][8] Previous observational effectiveness studies of fourth dose monovalent vaccination, primarily on data from before BA.4-5 subvariant predominance, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] also lend some indirect support to these recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Previous observational studies of fourth doses are primarily limited to the monovalent mRNA Covid-19 vaccines and mainly during periods prior to the emergence of the current predominating omicron subvariants BA.4 and BA.5. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] As such, data on the effectiveness of the bivalent mRNA-vaccines are needed to guide Covid-19 vaccination policy and to evaluate the benefit of developing variant-adapted Covid-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%